Investigation of reflecting discharge with the sectioned metal-hydride hollow cathode - Borisko, V.N.; Klochko, Ye.V.; Sereda, I.N.; Tseluyko, A.F.; Zinov'ev, D.V. (Вопросы атомной науки и техники, 2005)
In this paper the investigations of Penning discharge with the sectioned hollow cathode in hydrogen environment were carried out. As constructional elements of the hollow cathode the Zr50V50 alloy, which is able to absorb hydrogen reversibly was used. Using metal-hydride cathode was shown to allow to reduce the voltage of hollow cathode mode exciting. The possibility of hollow cathode mode operating by means of variation of potentials on its sections was investigated. У роботі проведені дослідження розряду Пенінга в середовищі водню із секціонованим порожнистим катодом. Як конструкційні елементи порожнистого катода використовувався сплав Zr50V50, здатний до оборотного поглинання водню. Показано, що застосування металогидрідного порожнистого катода дозволяє зменшити напругу збудження ефекту порожнистого катода. Досліджено можливість керування режимом порожнистого катода шляхом варіювання потенціалами на його секціях. В работе проведены исследования разряда Пеннинга в среде водорода с секционированным полым катодом. В качестве конструкционных элементов полого катода использовался сплав Zr50V50, способный к обратимому поглощению водорода. Показано, что применение металлогидридного полого катода позволяет уменьшить напряжение возбуждения эффекта полого катода. Исследована возможность управления режимом полого катода путем варьирования потенциалами на его секциях.